The Influence of Organizational Support and Meaningful Work on Work Engagement at the Environmental Office of Cirebon Regency - Tian Galuh Intan; Sunimah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the influence of organizational support and meaningful work on work engagement among employees at the Environmental Office of Cirebon Regency. The background of this study highlights the phenomenon of unequal workload distribution, which has an impact on the decline of employee work engagement in the public sector. Using a causal associative quantitative approach, data were collected through questionnaires from 110 respondents selected using a simple random sampling technique with the Slovin formula. The results of multiple linear regression analysis show that both organizational support and meaningful work have a positive and significant influence on work engagement, both partially and simultaneously. Specifically, the meaningful work variable was found to have a more dominant influence than organizational support in shaping employee work engagement. The research model contributes 66.2% to the work engagement variable, while the remaining percentage is influenced by other factors outside the model. These findings emphasize that the integration of organizational system support and the internalization of work meaning is a key strategy for improving the dedication and professionalism of civil servants in facing bureaucratic challenges at the regional level.